HUBUNGAN KADAR BETA SEKRETASE BETAAMILOID DAN HIDROKSINONENAL PLASMA DENGAN GANGGUAN KOGNITIF PASCASTROKE ISKEMIK - Yuliarni Syafrita,* Yanwirasti,** M Hasan Machfoed,*** Darwin Amir* (NEURONA, 2015)
INTRODUCTION THE LEVEL OF BETAAMYLOID A IN THE CEREBROSPINAL FLUID CSS CAN BE USED AS A MARKER TO DETECT COGNITIVE IMPAIRMENT SINCE CSS RETRIEVAL TECHNIQUE IS INVASIVE IT IS NECESSARY TO FIND RELATIVELY EASY CHEAP AND RELIABLE MARKERS